Measurement of V̄μ charged-current single π-production on hydrocarbon in the few-GeV region using MINERvA - Le, T.; Akbar, F.; Aliaga, L.; Andrade, D.A.; Ascencio-Sosa, M.V.; Bashyal, A.; Bercellie, A.; Betancourt, M.; Bodek, A.; Bonilla, J.L.; Bravar, A.; Budd, H.; et al. (American Physical Society, 2019)
The antineutrino scattering channel V̄μCH → μ⁺π⁻X (nucleon(s)) is analyzed in the incident energy range 1.5 to 10 GeV using the MINERvA detector at Fermilab. Differential cross sections are reported as functions of μ⁺ momentum and production angle, π⁻ kinetic energy and production angle, and antineutrino energy and squared four-momentum transfer. Distribution shapes are generally reproduced by simulations based on the GENIE, NuWro, and GiBUU event generators, however GENIE (GiBUU) overestimates (underestimates) the cross section normalizations by 8% (10%). Comparisons of data with the GENIEbased reference simulation probe conventional treatments of cross sections and pion intranuclear rescattering. The distribution of nontrack vertex energy is used to decompose the signal sample into reaction categories, and cross sections are determined for the exclusive reactions μ⁺π⁻n and μ⁺π⁻p. A similar treatment applied to the published MINERvA sample V̄μCH → μ⁺π⁰X[nucleon(s)] has determined the μ⁺π⁰n cross section, and the latter is used with σ(π⁻n) and σ(π⁻p) to carry out an isospin decomposition of V̄μ-induced CC(π). The ratio of magnitudes and relative phase for isospín amplitudes A₃ and A₁ thereby obtained are: Rᶹ̄ = 0.99 ± 0.19 and ϕᶹ̄ = 93° ± 7°. Our results are in agreement with bubble chamber measurements made four decades ago.
Keywords: Physics; Energy (signal processing); Isospin; Nucleon; Pion; Nuclear physics; Bar (unit); Particle physics; https://purl.org/pe-repo/ocde/ford#1.03.03